Evaluación del impacto de las ventas en la Empresa Banariego S.A. ubicada en la ciudad de Babahoyo provincia de los ríos en el periodo 2022. - Vera Castro, Jostin Elian (2023)
This study focuses on the impact of sales and its profitability within the company Banariego S.A. located in the city of Babahoyo, based on the importance of analyzing and improving sales strategies, especially in an accelerated and variable business environment in which the need to plan quantifiable and temporary sales objectives that provide the necessary relevance to be used in making informed decisions is created. The willingness to measure the growth or decline in sales margin to evaluate the financial performance of the company is reflected in the sales projection through historical analysis and statistical models. In addition, the influence of seasonal and climatic factors on the business, especially in the case of Banariego S.A., is highlighted. This study analyzes Banariego S.A.'s sales by using a descriptive approach and an inductive-deductive methodology to examine and improve the company's performance. Quantitative and qualitative information will be collected through surveys of sales personnel and finally the results will validate the theoretical research and help to improve the company's financial position